PENGARUH EMPLOYEE RETENTION DAN TURNOVER INTENTION TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA KOSPIN JASA CABANG JAWA TIMUR - Halimatus Sa’diyah; S Anugrahini Irawati; - faidal (Universitas Trunojoyo Madura, 2017)
The purposes of this study are (1)Employee Retention test whether variables affect the performance of employees at Kospin Services Branch of East Java. (2) To determine whether the variable turnover intention influence on the performance of employees at Kospin Services Branch of East Java. (3) To determine whether job satisfaction variables affect the performance of employees at Kospin Services Branch of East Java. (4) To determine whether a variable Employee Retention effect on job satisfaction in Kospin Services Branch of East Java.(5) To determine whether the variable Turnover Intention effect on job satisfaction. (6) To determine whether a variable Employee Retention mediating influence on employee performance through job satisfaction in Kospin Services Branch of East Java. (7) To determine whether the variable Turnover Intention mediating influence on employee performance through job satisfaction in Kospin Services Branch of East Java. Respondents in this research used a sample of 140 respondents.The method used in this research is multiple linear regression analysis and path analysis.Using this method, the results indicate that (1) Partially Employee Retention Variable has positive and significant effect on employee performance variables. (2) Partially Turnover Intention variable has positive and significant effect on employee performance variables. (3) Partially Job satisfaction variables has positive and significant effect on employee performance variables. (4) Partially Employee Retention variable has positive and significant effect on job satisfaction variables. (5) Partially Turnover Intention variable has positive and significant impact on job satisfaction variables. (6) Variable Employee Retention can directly affect the performance of the employee and the indirect effect through job satisfaction. (7) Turnover Intention variables can directly affect the performance of the employee and the indirect effect through job satisfaction.